EFEKTIFITAS PELAKSANAAN PIJAT EFFLUARAGE PADA IBU BERSALIN DI KLINIK PRATAMA DELIANA - Juli Selvi Yanti; Eka Maya Saputri; Wika Pratiwi (Ensiklopedia of Journal, 2021)
Effleurage massage is a light massage using the fingers, usually on the stomach, in tune with the breathing during contractions. Effleurage can be done by the mother herself or a labor companion during the contraction. Labor pain can cause hyperventilation, resulting in increased oxygen demand, increased blood pressure, and reduced intestinal and bladder motility. This situation will stimulate an increase in catecholamines which can cause interference with the strength of uterine contractions resulting in uterine inertia. If labor pain is not resolved, it will cause prolonged labor (Anita, 2017). The purpose of this study was to determine the effectiveness of period effleurage in maternal. This type of research is Quasi experimental. The population in this study were mothers who gave birth at the Pratama Deliana Clinic Pekanbaru. The results showed that effleurage massage was effective in reducing labor pain in women with a p-value of 0.002 (